Nurse Manager Competency Model in a Teaching Hospital - Setiawan Setiawan; Dewi Elizadiani Suza; Farida Linda Sari Siregar (Universitas Airlangga, 2021)
Introduction: Nurse managers in carrying out their duties must have a variety of competencies, one of which is managerial competencies. A model of competency for nurse managers will assist them in shaping their roles as managers in a teaching hospital. This study aims to develop the managerial competency model for nurse managers at the teaching hospital.Methods: The research design used in this study was action research. This research was conducted with 20 nurse managers who work at inpatient wards of the teaching hospital. Participants were selected by purposive sampling approach and have accepted to participate in the research. The data were obtained by using interview through focus groups discussions. The content analysis method was employed for analyzing the data. Results: This study found six domains of managerial competencies of nurse managers: 1) provision of patient care (assignment methods, clinical excellence, collaborators, patient safety, evidence-based practice), 2) resource management (personnel management, information and technology management, equipment management, supplies management), 3) leadership (commitment, conflict resolution, negotiator, role model, professional mentor, initiator, motivator), 4) self and staff development (effective communication skills, interpersonal relationship skills, tridharma function of nurses), 5) customer and service orientation (team builder, customer service, quality improvement), and 6) function of preceptorships (basic teaching skills, clinical skills). These 24 fundamental competencies are rooted in caring foundation.Conclusion: Nurse managers in teaching hospitals should possess a set of managerial competencies to perform their optimal roles in order to achieve the unit goals. This model will provide comprehensive and solid ways for nurse managers to improve their performance. Therefore, the set of nurse manager competencies needs to be standardized across the setting.